Determinant Variables Of Consumers’ Preference Towards Patanjali Products - Wagle, Sudip (Journal of Balkumari College, 2022)
Patanjali Ayurveda is maker of ayurvedic consumer product and is one of the fastest growing consumer company. Consumers of Twenty-first Century are much more health conscious and are always inclined to maintain quality of life. So, people are moving towards herbal and ayurvedic products. In order to purchase a product, consumer will go through a process of buying behavior. The purchase decision of consumer is mostly affected by the quality, price, packaging, advertisement, brand image and benefits offered by the brand. This study elucidate about the consumer’s preferences towards Patanjali products within Bharatpur Metropolitian city. Descriptive and casual comparative research design were used and the collected primary data via well-structured google form questionnaire were analyzed using both descriptive and inferential analysis. The major finding of this study shows brand image is the main reason that induces consumers to buy Patanjali products and it also reveals the level of satisfaction of consumers towards Patanjali products. Likewise, results reveals that the impact of quality, brand image, packaging and availability of products on consumers’ preference towards Patanjali products is found positive with significant whereas the impact of price on consumers’ preference towards Patanjali products is only positive with insignificant. Similarly, the influence of advertisement and offers on consumers’ preference towards Patanjali products is found negative but that is also insignificant.